2011
DOI: 10.1158/1940-6207.capr-10-0382
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Prevents Development of Medroxyprogesterone Acetate-Accelerated 7,12-Dimethylbenz(a)anthracene-Induced Mammary Tumors in Sprague–Dawley Rats

Abstract: The use of progestins as a component of hormone replacement therapy has been linked to an increase in breast cancer risk in postmenopausal women. We have previously shown that medroxyprogesterone acetate (MPA), a commonly administered synthetic progestin, increases production of the potent angiogenic factor vascular endothelial growth factor (VEGF) by tumor cells, leading to the development of new blood vessels and tumor growth. We sought to identify nontoxic chemicals that would inhibit progestin-induced tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
6
24
0
Order By: Relevance
“…Similar observations were made by Mafuvadze et al [20] in DMBA-induced progestin-accelerated rat mammary tumors and by Gupta et al [52], who suggested that apigenin may exert different effects on prostate cancer cells than on normal cells. By virtue of its ability to selectively induce apoptosis in rapidly growing breast cancer cells, while having no effect on normal mammary cells, apigenin would seem to be an extremely promising chemotherapeutic agent.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar observations were made by Mafuvadze et al [20] in DMBA-induced progestin-accelerated rat mammary tumors and by Gupta et al [52], who suggested that apigenin may exert different effects on prostate cancer cells than on normal cells. By virtue of its ability to selectively induce apoptosis in rapidly growing breast cancer cells, while having no effect on normal mammary cells, apigenin would seem to be an extremely promising chemotherapeutic agent.…”
Section: Discussionsupporting
confidence: 83%
“…As previously noted in the rat model for DMBAinduced MPA-accelerated mammary gland tumors [20], (Fig. 3), suggesting that apigenin specifically inhibits proliferation of tumor cells.…”
Section: Apigenin Prevents Progression Of Mpa-dependent Bt-474 Xenogrsupporting
confidence: 83%
See 2 more Smart Citations
“…Indeed, the HPLC profile obtained from the aqueous extract of M. deserti (Figure 2), showed the apigenin as a free flavone, which may explain the high anti-inflammatory effect of the aqueous extract of aerial parts of M. deserti. Works of Mafuvadze et al (2011) suggested that apigenin has important chemopreventive properties for breast cancer, through its anti-inflammatory activity. In conclusion, this study showed that the aqueous infusion extract of M. deserti possess a good anti-inflammatory activity which is confirmed by the inhibition of carrageenin-induced paw oedema.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%